Association of BMI with general health, working capacity recovered, and post-acute sequelae of COVID-19 - Peter, Raphael Simon; Nieters, Alexandra; Brockmann, Stefan O.; Göpel, Siri; Kindle, Gerhard; Merle, Uta; Steinacker, Jürgen M.; Kern, Winfried V.; Rothenbacher, Dietrich (Obesity, 2023)
The aim of this study was to determine the risk of post-acute sequelae of COVID-19 associated with the continuous spectrum of BMI.
Online veröffentlicht: 04. Oktober 2022
Gesehen am 05.12.2023